Effect 17α-Metiltestosterone Hormone with Different Dosage to Percentage Male Sex, Absolute Weigh Growth, and Survival to Congo Tetra Fish (Micraleptus interruptus) - Irfan, Muhammad; Abdullah, Nursanti; Paputungan, Siti Fadilla (Agrikan: Jurnal Agribisnis Perikanan, 2020)
Congo Tetra fish is one of the freshwater ornamental fish species which is in great demand because of its high economic value. Male congo tetra fish have a higher selling value than female fish, because the morphology of their bodies looks more attractive, especially their brighter colors and long fins. Sex reversal technology is one technique that can be used to obtain male monosexual offspring.The hormone 17α-methyltestosterone in male fish can increase spermatogenesis and determine secondary sex markers in male fish through the formation of sexual characteristics in fish morphology and body color. The administration of the hormone 17α-methyltestosterone with the right dose can increase the percentage of male sex of Congo Tetra fish. The purpose of this study was to determine the effect of the hormone 17α-methyltestosterone with different doses on the percentage of male sex, absolute weight growth, and survival of congo tetra fish, to determine which 17α-methyltestosterone hormone dose had the best effect on the percentage of male sex, growth in absolute weight, and survival in congo tetra fish. This research was conducted at the Regional Technical Service Unit of the Fish Seed Center for Ternate City. The time for conducting the research starts from March to May, 2020. In this study, 4 treatment doses of hormones were used, each treatment was repeated 3 times. The treatments tried were as follows: Treatment A: Dose 2 mg/l, Treatment B: Dose 3 mg/l, Treatment C: Dose 4 mg/l, Treatment D: Dose 0 mg/l (control).The results showed that the hormone 17α-methyl testosterone with different doses had a very significant effect on the male sex percentage of congo tetra fish, but it was not significantly different on the growth in absolute weight and survival of congo tetra fish. The highest average percentage of male sex in congo tetra fish was found in treatment C (dose 4 mg/l) which was 86.6%, the highest average value of growth in absolute weight was found in treatment A (hormone dose 2 mg/l) of 1.083 g, and the highest survival was found in treatment D (control) of 90.473%.